ANALISIS PENGARUH PENGETAHUAN TENTANG RIBA TERHADAP KEPUTUSAN MEMILIH MEMBUKA REKENING DI BANK SYARIAH - Indah Kartikasari (AN NUQUD, 2023)
The purpose of this study was to determine whether there is an influence of Knowledge About Usury on the Decision to Open an Account at an Islamic Bank. The type of research used is to use a quantitative approach. Data collection was carried out by distributing questionnaires to 46 respondents who had studied or understood knowledge about usury. The sampling technique used is proportionate simple random sampling While for the type of data using primary data and secondary data. The data obtained were analyzed by data analysis techniques, namely data validity test, data reliability test, data normality test, t test (partial) and determination coefficient test. From the hypothesis test this research stated Ha (accepted), meaning that there is an influence of knowledge about usury (X) on the decision to choose to open an account at an Islamic bank (Y). And from the results of the t test there is a significance value of 0.000 which means less than 0.05. Then the variable (X) student knowledge about usury affects the variable (Y) the decision to choose to open an account at an Islamic bank by 0.441 or 44.1% and the remaining 55.9% is influenced by other variables not included in this study